2017
DOI: 10.3390/ijms18051044
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Is Involved in Connective Tissue Growth Factor-Induced Proliferation, Migration and Overproduction of the Extracellular Matrix in Keloid Fibroblasts

Abstract: Adiponectin, an adipocyte-derived hormone, exerts pleiotropic biological effects on metabolism, inflammation, vascular homeostasis, apoptosis and immunity. Recently, adiponectin has been suggested to attenuate the progression of human dermal fibrosis. Connective tissue growth factor (CTGF) is induced in keloids and is thought to be participated in the formation of keloid fibrosis. However, the roles played by adiponectin in keloids remain unclear. In this study, we explored the effects of adiponectin on CTGF-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…As these pathological aspects of keloids are mediated by growth factors, including TGF-β, PDGF, VEGF, and bFGF, drug treatments are likely to inhibit the functions of these factors. For example, CTGF, a growth factor downstream of TGF-β [ 35 , 36 ], was found to be downregulated at both the gene and protein levels, which may account for the inhibition of cell proliferation and matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…As these pathological aspects of keloids are mediated by growth factors, including TGF-β, PDGF, VEGF, and bFGF, drug treatments are likely to inhibit the functions of these factors. For example, CTGF, a growth factor downstream of TGF-β [ 35 , 36 ], was found to be downregulated at both the gene and protein levels, which may account for the inhibition of cell proliferation and matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 For instance, connective tissue growth factor (CTGF), was demonstrated to be involved in intracellular signaling pathways in KFs. 41 It was found that CTGF could stimulate proliferation, migration, and accumulation of ECM produced by KFs. Further, it was also revealed that adiponectin suppresses' CTGF-induced KFs proliferation, migration, and ECM production with resultant attenuation of CTGF-induced phosphorylation of adipoR1 (adiponectin receptor 1), adenosine monophosphate-activated protein kinase (AMPK) mitogen activated protein kinase (p38), and extracellular-regulated kinase (ERK) signaling pathways.…”
Section: Two-dimensional Monolayer Culture Modelsmentioning
confidence: 99%
“…The progression of wound healing, including skin, is called the wound process and includes three stages: inflammation, proliferation with the formation of granulation tissue, and remodeling or fibrosis. (15) Wound healing without scarring is possible only in fetuses in the first 6-7 months of pregnancy due to the absence of the inflammatory phase of the wound process. (16) It is inflammation that plays a key role in the morphology of the future scar.…”
Section: Discussionmentioning
confidence: 99%